Ideal Concepts Implementation of Good Governance in the Land Registration Process by PPAT Based Justice Value - Desi Kumalasari; Edith Ratna (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The administration of government based on the principles of good governance is the basis for formulating and implementing democratic state policies. Good governance is a conception of the administration of a clean, democratic and effective government by the ideals of the formation of civil society. Good governance is closely related to the contribution, empowerment and balance between the three pillars: the government, the private sector and the community. By understanding the things mentioned above, it is important to discuss the formulation of the implementation of good governance in the context of implementing land registration by PPAT as one of the parties who has the authority to carry out land registration, especially the maintenance of land data so that it can provide better services to the community. The results of the study indicate that the implementation of Good Governance in the Land Registration process by PPAT is based on the Value of Justice, then the principles of good governance should be enforced in various important government institutions. These principles include: Community participation, upholding the rule of law, transparency, care and stakeholders, -oriented, equality, effectiveness and efficiency, accountability, and strategic vision, so that what Indonesia desires becomes a country and good governance can be realized, and the disappearance of factors Political interests, KKN, unfair justice, working outside the authority, and lack of integrity and transparency are some of the problems that make good governance still not achieved.